PREVALENCIA DE Giardia sp. EN CANES DE LOS DISTRITOS DEL CONO SUR DE LIMA METROPOLITANA - Zárate R., Daniel (2003)
The object of this study was to assess the prevalence of Giardia sp. in domestic canines from the Southern part of Lima, Peru. A total of 204 fecal samples from canines of the districts of Surco, Barranco, Chorrillos, San Juan de Miraflores, Villa María del Triunfo and Villa El Salvador were recolected. The animals were stratified according to the socioeconomic level of the owner. Samples were analized by the direct examination test and by the spontaneous sedimentation test for detection of Giardia sp. The direct examination test showed 8.8 ± 3.9% (18/204) of positive samples whereas the spontaneous sedimentation test gave a prevalence of 15.7 ± 5.0 (32/204). The latter test showed to be more sensitive than the direct examination test when results were compared by the McNemar test. The Logistic Regression test failed to show a significative relationship between presence of Giardia sp. and socioeconomic level of the owner or sex of animal. Puppies (<1 year old) were more affected than adults (>1 year). Likewise, parasitic forms were more frequently detected in soft than in normal feces. The results indicated the existence of a moderate prevalence of Giardia sp. infection in canine population of the Southern part of Lima City, suggesting that canine giardiasis in Lima would be a serious problem of Public Health.